Strategi Komunikasi Pemasaran Melalui Media Sosial Instagram - Wijayanto, Ahmad Syahri; Nursanti, Siti; Budhiharti, Tri Widya (CV. ITTC INDONESIA, 2024)
This research was conducted to determine the marketing communication strategies applied by Calceamenta in increasing the number of consumers on Instagram. The implementation of the strategies by Calceamenta is driven by the growing shoe-cleaning service business, as there is a rising need for shoe cleaning among the public who lack the time to do it themselves. The subjects of this study are the owners and employees of Calceamenta who have the authority to decide on the marketing communication strategies used by Calceamenta on Instagram, as well as supporting informants such as consumers and Instagram followers of Calceamenta. The data were obtained through a qualitative approach, using observation and interviews with the informants.The results of this study indicate that Calceamenta has implemented marketing communication strategies by utilizing Instagram social media to increase its service users. Calceamenta employs a marketing mix including Advertising, Sales Promotion, Public Relations, and Personal Selling. The results of this study show that Calceamenta uses new media such as Instagram as its marketing communication medium, driven by the owner’s perception that many people are already actively using Instagram. Calceamenta makes various efforts to capture the attention of the audience, who are their target potential consumers. The interest of potential consumers is built through Instagram content such as education, promotions, and testimonials from customers who have previously used Calceamenta’s services. The desire is emphasized by showcasing that potential consumers need Calceamenta’s services. The action refers to the decision of potential consumers to use Calceamenta’s services.